Surgery for Primary Hyperparathyroidism: Adherence to Consensus Guidelines in an Academic Health System. Issue 1 (January 2019) - Kuo, Eric J.; Al-Alusi, Mostafa A.; Du, Lin; Shieh, Albert; Livhits, Masha J.; Leung, Angela M.; Yeh, Michael W.
Abstract : Objective: To determine the extent to which consensus guidelines for surgery in patients with primary hyperparathyroidism (PHPT) are followed within an academic health system. Background: Previous studies have shown that adherence to consensus guidelines in community practice is low. Methods: Adults with biochemically confirmed PHPT who received primary care within an academic health system were identified from 2005 to 2015. Multivariable logistic regression was used to analyze predictors of parathyroidectomy (PTx). Results: In 617 patients, the overall PTx rate was 30.8%. When individual consensus criteria were examined, age <50 ( P <0.01), serum calcium >11.3 mg/dL ( P < 0.01), and hypercalciuria ( P = 0.02) were associated with PTx; while nephrolithiasis ( P = 0.07) and osteoporosis ( P = 0.34) did not affect the PTx rate. The PTx rate increased with the number of consensus criteria satisfied (1 criterion, 33%; 2 criteria, 45%; 3 or more criteria, 82%, P < 0.01). Independent predictors of PTx included male sex [odds ratio (OR) 1.7, 95% confidence interval (CI) 1.1–2.8], increasing serum parathyroid hormone (OR 1.1 per 10 pg/mL 95% CI 1.05–1.13), and endocrinologist evaluation (OR 1.6, 95% CI 1.1–2.4); while Black race (OR 0.4, 95% CI 0.2–0.8), lack of 24-hour urine calcium measurement (OR 0.5, 95% CI 0.3–0.8), Charlson Comorbidity Index ≥ 2 (OR 0.6, 95% CI 0.4–0.9), and age ≥80 years (OR 0.2, 95% CI 0.1–0.4) predicted against PTx. Conclusion: Within an academic health system, consensus guidelines do appear to influence the decision for surgery in patients with PHPT. However, the level of compliance is generally low, and similar to that observed in community practice.